Body image and quality of life of breast cancer patients: influence of timing and stage of breast reconstruction. Issue 9 (10th September 2015) - Teo, Irene; Reece, Gregory P.; Christie, Israel C.; Guindani, Michele; Markey, Mia K.; Heinberg, Leslie J.; Crosby, Melissa A.; Fingeret, Michelle Cororve
Abstract: Objective: The process of cancer‐related breast reconstruction is typically multi‐staged and can take months to years to complete, yet few studies have examined patient psychosocial well‐being during the reconstruction process. We investigated the effects of reconstruction timing and reconstruction stage on body image and quality of life at specific time points during the breast reconstruction process. Methods: In this cross‐sectional study, 216 patients were grouped into four reconstructive stages: pre‐reconstruction, completed stage 1, completed stage 2, and final stages. Multiple regression analyses examined the roles of reconstruction timing (immediate vs delayed reconstruction) and reconstruction stage as well as their interaction in predicting body image and quality of life, controlling for patient age, BMI, type of reconstruction, chemotherapy, radiation therapy, and major complication(s). Results: A difference in pattern of body image was observed across the reconstructive stages, with those receiving delayed reconstruction showing significant decrease in body image dissatisfaction compared with those with immediate reconstruction. At pre‐reconstruction, patients awaiting delayed reconstruction reported significantly lower social well‐being compared with those awaiting immediate reconstruction. Reconstruction stage predicted emotional well‐being, with higher emotional well‐being observed in those who had commenced reconstruction. Conclusions: Timing and stage of reconstruction are important to consider when examining psychosocial outcomes of breast cancer patients undergoing reconstruction. Those waiting to initiate delayed reconstruction appear at particular risk for body image, emotional, and social distress. Our findings have implications for delivery of psychosocial treatment to maximize body image and quality of life of patients undergoing cancer‐related breast reconstruction.Copyright © 2015 John Wiley & Sons, Ltd.